Diagnostic value of chest spiral CT scan and Doppler echocardiography compared to right heart catheterization to predict pulmonary arterial hypertension in patients with scleroderma: Predicting pulmonary arterial hypertension in scleroderma - Kooranifar, Siavash; Naghshin, Roozbeh; Sezavar, Seyed Hashem; Hajsadeghi, Shokoufeh; Talebzadeh, Seyed Mehdi (Acta Biomedica Atenei Parmensis, 2021)
Background: Because of invasive nature of catheterization, using other noninvasive tools is more preferred to assess pulmonary arterial hypertension (PAH). The present study assessed the value of chest spiral CT scan and Doppler echocardiography compared to right heart catheterization (RHC) to predict PAH in patients with scleroderma. Methods: This cross-sectional study was performed on 15 patients with limited scleroderma. All subjects underwent Doppler echocardiography (to assess PAP) and chest spiral CT scan without injection (to assess pulmonary trunk length or PUL), followed by RHC to assess PAH. Results: Comparing PUL in spiral CT scan with PAP in RHC yielded a sensitivity of 75.0% and a specificity of 100% for predicting PAH. Similarly, comparing PAP value in echocardiography with PAP in RHC achieved a sensitivity of 100% and a specificity of 63.6% to discriminate PAH from normal PAP condition. Analysis of the area under the ROC curve showed high power of CT scan to predict PAH (AUC = 1.000). The best cutoff point for PUL to predict PAH was 29.95 yielding a sensitivity of 100% and a specificity of 100%. Also, ROC curve analysis showed high value of echocardiography to discriminate PAH from normal PAP status (AUC = 0.841) that considering a cutoff value of 22.88 for PAP assessed by echocardiography reached to a sensitivity of 72.7% and a specificity of 100%. Conclusion: Both chest spiral CT scan and Doppler echocardiography are very useful to diagnose PAH and its severity in patients with scleroderma.